ZnO nanonails: Organometallic synthesis, self-assembly and enhanced hydrogen gas production - Mohd Daud, S.N.H.; Haw, C.Y.; Chiu, W.S.; Aspanut, Z.; Chia, M.Y.; Khanis, N.H.; Khiew, P.; Hamid, M.A.A. (Elsevier, 2016)
We report the rational synthesis and characterizations of defect-rich zinc oxide (ZnO) nanonails that were prepared by organometallic approach and their implementation as an efficient photocatalyst for hydrogen (H2) generation. The ZnO nanonails were prepared from zinc stearate in n-octadecene that serves as non-coordinating solvent without the presence of any capping agent. Transmission electron microscopy (TEM) studies reveal that the individual triangular prismatic nanonail has an average edge length of 50–70 nm and it appears to have preferred growth orientation along [0001] crystal axis. Intriguingly, this nanonails show oriented-attachment along the flat-basal edge and self-assembled into twinned structure. Such structure is interconnected via a narrow-gap to form symmetrical twinned-like nanonails with truncated tips at both ends. In comparison to ZnO commercial nanopowder, ZnO nanonails show significant enhancement in photocatalytic H2 gas generation rate of 53.33% under UV light for 5 h. These results demonstrate ZnO nanonails to be a substantial potential photocatalyst for efficient photocatalytic applications.